Characterisation and pickling behaviour of thermal oxide scale on low carbon steel produced from a thin slab - Chandra-Ambhorn, Somrerk; Somphakdee, Tanongsak; Chandra-Ambhorn, Walairat (My University, 2011)
Thin slab interested in this work was the one with the thickness of ca. 50 mm and mainly made from recycled steel. Chemical composition of the studied steel strip produced from such slab was Fe with 0.077 wt% C, 0.233 wt% Mn, 0.191 wt% Si, 0.159 wt% Cu and 0.052 wt% Ni. Scale retained on that steel after hot rolling was studied. The hot-rolled sample was pickled in 10%v/v HCl aqueous solution at 80 °C. Weight loss and relative XRD peaks of hematite-per-iron and magnetite-per-iron were measured at different pickling periods of time. It was observed that the as-received scale was crack-free. Hematite-and-iron ratio approached zero at the pickling time of 3 seconds. Magnetite-per-iron ratio gradually decreased with increased pickling time and approached zero later. These results indicated that pickling solution attacked the outermost hematite layer resulting in removing of this layer first. Sublayers of scale consisting of magnetite were completely pickled later. Pickling behaviour was not merely volumetric since scale was crack-free. Mechanical adhesion of scale on steel substrate was additionally investigated by tensile test to help characterise the oxide scale. © (2011) Trans Tech Publications.
Keywords: Carbon steel; Mechanical adhesion; Pickling behaviour; Recycle; Thermal oxide scale